Manajemen Post-Dural Puncture Headache Menggunakan Teknik Blok Ganglion Sphenopalatina - Wisudarti, Calcarina Fitriani Retno; Mahmud; Gupta, Adista Yugadhyaksa (Jurnal Komplikasi Anestesi, 2021)
Post Dural Puncture Headache (PDPH) is a complication that can occur and be bothersome in patients undergoing neuraxial anesthesia. PDPH management includes conservative management such as hydration, caffeine, and oral analgesics to other invasive measures such as the Epidural Blood Patch (EBP). Sphenopalatine Ganglion Block (SPGB) is a technique to treat various kinds of headaches. The results showed that the SPGB technique improved PDPH symptoms although the data were not significant in some cases. We report a post-subarachnoid block patient who complained of PDPH symptoms. The patient's risk factor is the female gender. In this patient, an SPGB procedure was performed. Symptoms of PDPH were relieved after 17 days post-subarachnoid block procedure.